U-Th age evidence from carbonate veins for episodic crustal deformation of Central Anatolian Volcanic Province. (1st December 2017) - Karabacak, Volkan; Uysal, I. Tonguç; Ünal-İmer, Ezgi and Mutlu, Halim and Zhao, Jian-xin
Abstract: Central Anatolia represents one of the most outstanding examples of intraplate deformation related to both continental collision and back-arc extension generating non-uniformly distributed stress fields. In this study, we provide direct field evidence of various stress directions and investigate carbonate-filled fracture systems in the Central Anatolian Volcanic Province using U/Th geochronology and isotope geochemistry for evaluating the episodes of latest volcanic activity under regional stress. Field data reveal two independent fracture systems in the region. Successive fracture development has been controlled by two different volcanic eruption centers (Hasandağ Composite Volcano and Acıgöl Caldera). Trace element, and stable (C and O) and radiogenic (Sr) isotope compositions of carbonate veins indicate different fluid migration pathways for two different fracture systems. The U/Th age data for carbonate veins of two independent fracture systems indicate that the crustal deformation intensified during 7 episodic periods in the last 150 ka. The NNE-trending first fracture system was formed as a result of strain cycles in a period from 149 ± 2.5, through 91 ± 1.5 to 83 ± 2.5 ka BP. Subsequent deformation events represented by the ENE-trending second fracture zone have been triggered during the period of 53 ± 3.5, 44 ± 0.6 and 34 ± 1 ka BP before the first fracture zone resumed the activity at about 4.7 ± 0.15 ka BP. Although further studies are needed to evaluate statistical significance of age correlations, the periods of carbonate precipitation inferred from U-Th age distributions in this study are comparable with the previous dating results of surrounding volcanic eruption events. Graphical abstract: Highlights: Episodes of latest volcanic activity are dated for the first time with U/Th age data of carbonate veins. The recent deformation is in favor of extension with the effect of a NW-SE striking tension stress in the Central Anatolia. The crustal deformation intensified in at least 7 periods of the last 150 ka in the Central Anatolian Volcanic Province.